Analysis of genetic variants in myeloproliferative neoplasms using a 22-gene next generation sequencing panel - Tan, Jaymi (2021)
Introduction: Myeloproliferative neoplasms (MPNs) encompass a heterogeneous group of chronic clonal blood disorders with leukaemic potential. Chronic myeloid leukaemia (CML) is the only MPN with a specific molecular marker – the Philadelphia (Ph) chromosome. Driver mutations in JAK2, CALR and MPL have been discovered in Ph-negative MPNs. However, these mutations are neither subtype-specific nor predictive of clinical outcome. The discovery of other MPN-associated genes over the last decade has indicated to the potential utility of next-generation sequencing (NGS) technology in the clinical management of MPNs. The general objective of this study was to identify and confirm the spectrum of mutations in a small cohort of classic Ph-negative MPN (essential thrombocythaemia (ET), polycythaemia vera (PV), and primary myelofibrosis (PMF) samples using NGS. Methods: A custom NGS panel targeting the hotspot exons of 22 genes was designed and technically validated using reference standards. Peripheral blood samples and the clinical data of 10 MPN patients (ET n=3, PV n=3, PMF n=4) were obtained from three institutions (Sunway Medical Centre, Universiti Kebangsaan Malaysia Medical Centre, and Ampang Hospital). The samples were subjected to NGS and data analysis was conducted via a bioinformatics pipeline. Sanger sequencing was used to confirm the NGS-detected variants. Results: The evaluation of the custom NGS panel performance revealed a sensitivity, specificity, positive predictive value, intra-run concordance and inter-run concordance of above 95%, and a detection threshold of 1% variant allele frequency (VAF). Analysis of NGS data revealed that the custom NGS panel was able to detect a total of 44 polymorphisms and 20 unique variants across the 10 clinical MPN samples, 4 of which were putatively novel. In silico prediction of functional variants identified 3 of the 4 putative novel variants to be of potential biological significance. Most of the NGS-detected variants were confirmed via Sanger sequencing. The frequency of non-driver variants in the majority of JAK2 V617F-positive samples was found to be similar to that of CALR-positive samples. There were no significant associations between the frequencies of variants and the different MPN subtypes as well as clinical phenotypes. Conclusion: Although no subtype-specific mutational profiles were identified, the fidelity of the NGS analysis in this study supports its utility in mainstream genetic diagnostics. Future studies will need to include a larger cohort of samples with robust patient follow-up data and potentially profile a greater number of genes to further clarify if subtype-specific genotype-phenotype associations exist in these Ph-negative MPNs.